Knowledge, Attitude, and Practice Towards Antibiotic Use Among the Public in the City of Kuantan, Pahang State, Malaysia. - Muhammad Eid Akkawi; Nashaat Al-Shami; Yaser Mohammed Al-Worafi; Abdullah Abdulmajid Abdo Ahmed; Abdulkareem Mohammed Al-Shami (IIUM Press, International Islamic University Malaysia, 2022)
Background: Public knowledge and attitudes towards antibiotic use play a vital role in the success of controlling antibiotic resistance. This study aimed to assess the public's knowledge, attitudes, and practice (KAP) towards antibiotic use in Kuantan, Malaysia. Methods: This cross-sectional study was conducted among the general public above 18 years old. The data was collected in public places using a pre-validated questionnaire. Software Statistical Package for Social Sciences (SPSS) was used for statistical analyses. Results: Out of 410 participants who answered the questionnaire, 229 (55.9%) of them were female and 288 (70.3%) had a college/university degree. It was found that 258 participants (62.9%) have good knowledge and 306 of them (74.6%) have positive attitude towards antibiotic use. However, 160 respondents (39%) believe that antibiotics can kill viruses and 183 respondents (44.6%) stated that they would ask the doctor to give them antibiotics in case they have common cold symptoms. Having a good knowledge was significantly related to the age (P=0.005), employment status (P<0.001), education level (P<0.001), and the field of work or study (P<0.001). Furthermore, 313 of the sample (76.3%) had an overall good practice. However, 162 participants (39.5%) do not complete their antibiotic course. Additionally, 57 participants (13.9%) share and 69 of them (16.8%) use the leftover antibiotics. Showing a good practice correlated to the field of work/study (P =0.04), level of knowledge (Spearman's rho = 0.373; P<0.001) and attitude (Spearman's rho = 0.55; P<0.001). Conclusion: Although the majority of the public showed good KAP, there are still important gaps that need to be filled. Therefore, a public educational campaign is needed to improve the knowledge, attitude and practice towards antibiotic use.